Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1373/clinchem.2004.033274
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Genetic Variants of Transthyretin by Liquid Chromatography–Dual Electrospray Ionization Fourier-Transform Ion-Cyclotron-Resonance Mass Spectrometry

Abstract: Background:One of the numerous proteins causing amyloidosis is transthyretin (TTR), a protein usually responsible for the transport of thyroxine and retinolbinding protein. Variants within TTR cause it to aggregate and form insoluble fibers that accumulate in tissue, leading to organ dysfunction. Methods: TTR was immunoprecipitated from serum by use of a polyclonal antibody and subsequently reduced with tris(2-carboxyethyl)phosphine. The purified TTR was then analyzed by fast-gradient liquid chromatography-dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…However, there are several major plasma proteins besides albumin that contain unpaired Cys residues that may be available for disulfide formation with Cys and Hcy. Mass spectrometry has provided clear evidence that some of these proteins, such as transthyretin, apolipoprotein A-II, and apolipoprotein E, circulate as forms with amino acids or peptides attached via disulfides to the proteins (12)(13)(14)(15)(16)(17)(18)22 ). Major plasma proteins with unpaired Cys residues and reference concentration intervals in healthy persons are listed in Table 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are several major plasma proteins besides albumin that contain unpaired Cys residues that may be available for disulfide formation with Cys and Hcy. Mass spectrometry has provided clear evidence that some of these proteins, such as transthyretin, apolipoprotein A-II, and apolipoprotein E, circulate as forms with amino acids or peptides attached via disulfides to the proteins (12)(13)(14)(15)(16)(17)(18)22 ). Major plasma proteins with unpaired Cys residues and reference concentration intervals in healthy persons are listed in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have determined that some Hcy and Cys are linked to lipoproteins (11 ) or to unpaired Cys residues in transthyretin (12)(13)(14)(15)(16)(17)(18). These findings suggest the binding of Hcy and Cys to a variety of proteins via disulfide linkages (11)(12)(13)(14)(15)(16)(17)(18). The present study sought to determine the proportions of thiol-containing amino acids and peptides bound to albumin and globulins.…”
mentioning
confidence: 98%
“…Heterogeneity is observed for many components because of exopeptidase action on the peptide chain, sequence variations, and variable modifications of free sulfhydryl groups of unpaired cysteines (19,20,28,(65)(66)(67). In polypeptides with unpaired cysteine residues, such as subunits of transthyretin, apolipoprotein A-II, ␣ 1 -proteinase inhibitor, and albumin, disulfides may form with a variety of compounds, such as cysteine, cysteinylglycine, glutathione, or other polypeptides (dimerization of apolipoprotein A-II), or the sulfhydryl may undergo oxidation (19,20,28,(65)(66)(67). Proteins with unpaired cysteines also may link via disulfides to other proteins, as in the case of ␣ 1 -microglobulin, such that a mixture of different covalently bound forms of the protein is observed (68 ).…”
Section: Mass Assignments Of Plasma Componentsmentioning
confidence: 99%
“…Indeed, one of the most widely used methods for quantifying such mutations in DNA relies on the measurement of the mass of oligonucleotides differing at a single base (16). Prior studies have shown that it is possible to identify posttranslationally altered proteins using MS, as well as to identify highly abundant abnormal proteins, such as those responsible for amyloidosis (17)(18)(19)(20)(21)(22). In this work, we sought to develop an MS approach that could identify and quantify somatically mutant proteins in a generally applicable fashion.…”
mentioning
confidence: 99%